The Effect of The Use of Social Media (Whatsapp) towards The Biological Cognitive Learning Outcomes of Class XII MIA Students at SMA Negeri 1 Tinambung - Jirana, Jirana Jirana; Irfan, M; Damayanti, Mesra (Journal of Biological Science and Education, 2022)
Social media is one of the media that has several positive and negative values. It can be used as a learning medium but can also be a distraction in the learning process. This study aims to determine the effect of social media (WhatsApp) on students' cognitive learning outcomes.. This study uses a type of correlation research with a quantitative approach. The population in this study were all students of SMAN 1 Tinambung. The research sample was 99 students, obtained using a probability sampling technique with the simple random sampling method. The variables studied were: (1) The independent variable was the use of social media; (2) The dependent variable was learning outcomes.  Data collection techniques use questionnaires,  interviews, and documentation. The results showed a relationship between the use of social media (Whatsapp) and the cognitive learning outcomes of grade XII MIA students at SMA Negeri 1 Tinambung. This is evidenced by the correlation coefficient ( r) of 0.258, which is in the low category and the Pearson correlation value or r count (0.258) r table (0.1975) and the Sig value. (0.010) 0.05.  These results indicate that the effect shown is in a low category. It is hoped that further researchers who will do the same will be more prepared in terms of respondents' willingness. Keywords:  Social media, biology learning